Procedurally Generated Age-related Visual Deficits in Virtual Reality Environments - Zavlanou, Christina; Huber, P.; Tisserand, Y.; Rudrauf, D.; Lanitis, Andreas (My University, 2021)
The simulation of visual deficits associated with aging has been the subject of numerous investigations both in real environments with the use of aging suits and in immersive environments with the use of Extended Reality experiences. However, there is a dearth of heterogeneity and randomness, which characterize the age-related conditions and are important aspects in human-like simulations. Towards this end, procedurally generated age-related deficits are simulated in Virtual Reality environments, giving the possibility to experience these deficits and their nuances in real time. Our work is drawing upon state-of-the-art featurebased approaches, such as foveated rendering and procedural noise, to provide realistic effects. A pilot assessment is conducted through a visual performance task, while eye-tracking data are recorded. The preliminary results provide a first evaluation of the simulation’s effectiveness in …
Keywords: Compute shaders; Foveated rendering; Procedural noise; Virtual Reality; Eye-tracking